2003
DOI: 10.1097/00004872-200312000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rarefaction and abnormal cardiovascular reactivity in hypertension

Abstract: A reduced microvascular network may contribute to abnormal cardiovascular reactivity and to exercise-induced rheological abnormalities in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Hence, isoprostanes may contribute to development of capillary rarefaction, which has been observed in pathophysiological states of increased oxidative stress, such as CHD or systemic hypertension. 19,20 In our study, 8-iso-PGF 2␣ , 8-iso-PGA 2 , and 8-iso-PGE 2 inhibited the VEGF-induced angiogenic response via activation of the TBXA2R, because the TBXA2R antagonists SQ-29548, BM 567, and ICI 192,605 reversed isoprostaneinduced inhibition of angiogenesis (online data supplement). Besides pharmacological antagonism of the TBXA2R, we were able to demonstrate that lentiviral knockdown of TBXA2R also resolved the inhibitory effect of 8-iso-PGF 2␣ (online data supplement).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Hence, isoprostanes may contribute to development of capillary rarefaction, which has been observed in pathophysiological states of increased oxidative stress, such as CHD or systemic hypertension. 19,20 In our study, 8-iso-PGF 2␣ , 8-iso-PGA 2 , and 8-iso-PGE 2 inhibited the VEGF-induced angiogenic response via activation of the TBXA2R, because the TBXA2R antagonists SQ-29548, BM 567, and ICI 192,605 reversed isoprostaneinduced inhibition of angiogenesis (online data supplement). Besides pharmacological antagonism of the TBXA2R, we were able to demonstrate that lentiviral knockdown of TBXA2R also resolved the inhibitory effect of 8-iso-PGF 2␣ (online data supplement).…”
Section: Discussionmentioning
confidence: 56%
“…17,18 Moreover, several groups have demonstrated that patients at high cardiovascular risk, eg, hypertensive individuals, or patients with established CHD exhibit an impaired response to angiogenic stimuli and a rarefaction of the peripheral microvascular (capillary) bed. 19,20 Because recent experimental findings have indicated that synthetic TBXA2R mimetics may inhibit crucial steps of the angiogenesis, eg, the sprouting of new vessels from preexisting vessels, 21,22 we hypothesized that isoprostanes may contribute to vascular rarefaction by inhibiting angiogenesis via activation of the TBXA2R.…”
mentioning
confidence: 99%
“…Hypertension, a known complication of VEGFR signalling inhibition, is likely related with several factors, including diminished nitric oxide and prostacyclin synthesis (Scotland et al, 2005), diminished endothelial baroreceptor response (Yang et al, 2002), small artery and arteriole rarefaction (Ciuffetti et al, 2003) as well as increased vascular stiffness (Veronese et al, 2006). To our knowledge, this is the first clinical trial among malignant glioma patients to note an association between hypertension after VEGF-targeted therapy and improved outcome.…”
Section: Discussionmentioning
confidence: 84%
“…5 Substantial evidence indicates that microvascular rarefaction is associated with the pathogenesis of hypertension and may be accompanied by parenchymal cell death. 6,7 The disappearance of microvessels in hypertensive subjects may be a secondary event after blood pressure elevation. 8 However, recent research in man demonstrates microvascular rarefaction in pre-established stage of hypertensive subjects who still maintain near normal blood pressure.…”
mentioning
confidence: 99%